HEPATITIS B AND HEPATITIS C VIRUS IN WOMEN WITH FIRST PREGNANCY - Jadoon, Shandana Mustafa; Adeel, Muhammad; Aslam, Shaheen; Rasool, Ahsan (Journal of Ayub Medical College Abbottabad, 2017)
Background: Hepatitis B and Hepatitis C are amongst the leading causes of morbidity and mortality in pregnant women throughout the globe. This study is aimed at determining the frequency of these infections among primigravid females and the common factors that make them prone to these infections. Methods: This cross-sectional study was conducted at Ayub Teaching Hospital, Abbottabad from December 2015 to May 2016. A total of 174 jaundiced primigravida patients were included in the study through non-probability consecutive sampling. Blood samples were sent for HBsAg and anti-HCV ELISA. Samples were analysed by the pathologist with more than 5 years clinical experience. All data will be analysed using SPSS-16. Results: The mean age of the subjects was 24±5.7 years. Six (3.4%) patients were HBsAg positive and 13 (7.5%) were anti-HCV positive. About 9% of patients had undergone surgery in their life and 1.7% reported having received blood transfusion during their life. Thirty-two of them had history of intravenous or intramuscular injections. History of piercing of body part mostly ear-piercing for ornaments was present in 170 (97.7%) respondents. However, the frequency of blood transfusion, surgery and body piercing was not statistically significantly between HBsAg positive, HBsAg negative, and anti-HCV positive and negative patients (p>0.05). Conclusion: The incidence of these viral infections in our community is on the rise. It emphasizes the need of routine antenatal screening in pregnant ladies for these viruses and to educate the public about preventive measures against these infections. Keywords: Hepatitis B; Hepatitis C; Common factors, First pregnancy